Mise à jour de la matrice des coefficients de capital pour l’économie québécoise - Boyer, Marcel; Dagenais, Marcel; Downs, André; Sauriol, Gilles (L'Actualité économique)

(untitled) (HEC Montréal, 1981)
ABSTRACTThis paper presents a capital coefficient matrix for replacement and a capital coefficient matrix for expansion, for the Quebec economy disaggregated into 29 industrial sectors. The computations are based on data for the 1972-1976 period. The matrices presented in this paper constitute an up-dating of matrices presented in a similar study made in 1973 by the Centre de Recherche en Développement Économique. In order to perform this updating, we had the opportunity of using more reliable data series which were not available when the former matrices were estimated.